PERBEDAAN JENIS KELAMIN TERHADAP MINAT BERWIRAUSAHA MAHASISWA JURUSAN PENDIDIKAN EKONOMI UNIVERSITAS NEGERI SURABAYA - DAMAYANTI, NOVITA (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
The aim of this research is to find out whether or not there are differences between interest in entrepreneurship among men and women in the Department of Economics of Education, State University of Surabaya. This research uses the technique analysis of data t-test to determine whether two sample which it did not correlate having an average value different. t-test done by means of comparing differences between two average score with a standard error of the differences in average two samples. . It is based on the results of t count showed 0,789 with a P value of 0,432. The value of P value 0,432 > from 0.05 (α).It means : the average interest of entrepreneurship amongs women and men students in the Department of Economics State University of Surabaya did not differ significantly. Keywords : gender, interest of entrepreneur